Teacher Strategies in Facing Digital Transformation - Gresinta, Efri; Hidayat, Rais (Journal of Industrial Engineering & Management Research, 2024)
Education in the era of globalization really demands that all resources operating in the world of education, especially teachers, must quickly adapt to these conditions. This research aims to describe teachers’ strategies in facing digital transformation in the era of education 4.0 considering the important role of educators. The method used in this research is descriptive qualitative. This research was carried out at one of the Integrated Islamic Elementary Schools (SDIT) in East Jakarta using data collection techniques through interviews and observation. The research results show that teachers’ strategies in dealing with digital transformation are good through effective implementation in learning. The strategy carried out is through learning technology training by bringing in IT expert resource persons from several computer tutoring centers and colleagues regarding Google Class Room, Zoom Meeting, Google Meet, Sway, Canva, and video editing. Self-motivation and self-esteem make the strategies implemented in facing digital transformation work well. School support regarding IT infrastructure is very helpful in the implementation efforts carried out by teachers. The strategies carried out, the results have been implemented in the learning process for students. The obstacle in facing this strategy is the problem of an unstable internet connection. The main strategy that must be carried out concerns the capabilities of human resources and the infrastructure that is owned must be adapted to changes in needs that occur. Digital technology as a strategy must be well prepared so that digital transformation runs smoothly.